S6 Educational content and style of delivery in pulmonary rehabilitation (PR): a review. (December 2018) - Roberts, NJ; Kidd, L; Kirkwood, K; Cross, J; Partridge, MR
Abstract : Background: PR is a core component of COPD management with well recognised benefits. PR aims to equip participants with the right tools to take control of their condition and structured education features as a key approach to this. There is, however, significant variation in the content and delivery of education within PR programmes. The most recent guidance on pulmonary rehabilitation does not specify what should be delivered in detail on how it should be delivered in practice. 1 Methods: A systematic review was undertaken to identify the evidence base for educational sessions within pulmonary rehabilitation, examining content and method of delivery. MEDLINE, EMBASE, CINAHL, PsycINFO, ERIC, Cochrane Library, Open Grey and DaRE were searched from January 1981 – July 2017. A range of search terms and synonyms were used relating to 'pulmonary rehabilitation' and 'education'. Results: Fourteen studies were included; 7 were observational survey studies, 4 were quasi-experimental studies and 3 were RCTs. Five key topics featured in most of the studies including: Anxiety/depression and stress management Early recognition of signs of infection Dyspnoea and symptom management Nutrition Techniques using inhalers and nebulisers. Broader topics such as welfare and benefits, sexuality, and advance care directives did not frequently feature within the included studies. Five studies reported use of lectures although studies have shown that participants prefer to have smaller interactive group sessions. Only four studies used tools to measure knowledge or learning pre and post rehabilitation. The publication dates range from 1988–2017, and therefore represent the improvements made to delivery of PR over that time period. Conclusions: The delivery of pulmonary rehabilitation education is variable and doesn't follow suggested educational talks. 1 There was no guidance around how education should be delivered and by whom and how this should be tailored according to learning needs and literacy levels. Guidance on core education topics and delivery is needed taking a patient centred motivational approach to ensure education is delivered effectively. Further research into appropriate educational outcome measures are needed to ensure behaviour change associated with education are captured. Reference: Bolton CE, et al. Thorax2013;68:ii1–30.